THE RELATIONSHIP BETWEEN THE SUPPORT OF COMMUNITY LEADERS AND FAMILY SUPPORT WITH THE INTEREST OF ADOLESCENTS IN PARTICIPATING POSBINDU PTM IN PURO VILLAGE PUSKESMAS KARANGMALANG SRAGEN: HUBUNGAN ANTARA DUKUNGAN TOKOH MASYARAKAT DAN DUKUNGAN KELUARGA DENGAN MINAT REMAJA MENGIKUTI POSBINDU PTM DI DESA PURO PUSKESMAS KARANGMALANG SRAGEN - Alifia Ayu Romadhona Suparno; Anisa Catur Wijayanti (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2024)
Abstract Background: Non-communicable disease are the leading cause of global death. The biggest causes of death are cardiovasculer disease, cancer, chronic respiratory disease and diabetes. Indonesia it self has experienced a significant incease in PTM the prevalence of PTM has increased, namely high blood pessure. Objectives: The aim of the research is to analyze the relationship between community leaders and family support with the interest of teenagers participating in the PTM Posbindu in Puro Village, karangmalang Jealth center, Sragen, in 202. Research Metodes: observasional quantitative research with cross sectional approach, the population is is adolescents aged 15-19 years, the sample in this study wes 252 respondents, the sampling technique used purposive sampling technique. Results: the results of this study found that there wes a relationship between the support of community leaders p<0.001 and family support p<-.001 with adolescent interest in participating in the PTM Posbindu in Puro karangmalang Village, Sragen Conclusion: tahe conclusion there is a relationship between the support of community leaders and family support for the interest of teenagers attending in PTM Posbindu in puro Village. Keywords: Community Leaders Support, Family Support, Youth Interest